2009
DOI: 10.1007/s00025-008-0326-0
|View full text |Cite
|
Sign up to set email alerts
|

The Good Quotient of the Semi-Stable Foliations of $${\mathbb{CP}}^2$$ of Degree 1

Abstract: Let F1 = PH 0 (CP 2 , T CP 2 ) be the space of foliations of CP 2 of degree 1, i.e., the projective space of vector fields of CP 2 . We consider the linear action P GL(3, C) × F1 → F1, (g, X) → gX = DgX • (g −1 ). We prove that the Good Quotient of the semi-stable points for this action is CP 1 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…We will deal only with one-dimensional singular foliations of P 2 k from now on, and will thus drop the adjective "singular." Taking duals in the Euler sequence (1), we obtain the exact sequence…”
Section: Singular Foliationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We will deal only with one-dimensional singular foliations of P 2 k from now on, and will thus drop the adjective "singular." Taking duals in the Euler sequence (1), we obtain the exact sequence…”
Section: Singular Foliationsmentioning
confidence: 99%
“…It was using this criterion that Goméz-Mont and Kempf [8] have shown that a foliation whose all singular points have Milnor number 1 is stable, that is, corresponds to a stable point of F m . And Alcántara [1], [2] has characterized the semi-stable foliations of degrees 1 and 2.…”
Section: The Actionmentioning
confidence: 99%
See 1 more Smart Citation